Three dimensional printing-assisted biplane stereotomy to treat severe varus knee with femoral deformity: a technical note - Shuai-Jie Lv; Xu-Song Li; Zhao-Kai Jin; Xun Liu; Jun Ying; Yi Tang; Pei-Jian Tong; Jie-Feng Huang; Ya-Hong Zhu (BMC Musculoskeletal Disorders)
Abstract Double level osteotomy (DLO) is recommended for severe varus knees with deformities in both the femur and tibia or the deformity angle is greater than 20˚. with the assistance of preoperative computer planning and intraoperative 3D printing guides, DLO was successfully completed on the femoral and tibial sides. Meanwhile, the lateral osteotomy angle was intentionally increased by 2˚ to reduce the potential risk of instability in the posterior lateral knee joint. The last follow-up showed the VAS and KOOS decreased from 5 to 193 to 0 and 84. The ROM and KSS increased from 115 ° and 128 to 120° and 199.